2020
DOI: 10.1038/s41598-020-77600-2
|View full text |Cite
|
Sign up to set email alerts
|

Genetic mapping and candidate gene analysis for melon resistance to Phytophthora capsici

Abstract: Phytophthora blight is one of the most serious diseases affecting melon (Cucumis melo) production. Due to the lack of highly resistant germplasms, the progress on disease-resistant research is slow. To understand the genetics of melon resistance to Phytophthora capsici, an F2 population containing 498 individuals was developed by crossing susceptible line E31 to highly resistant line ZQK9. Genetic analysis indicated that the resistance in ZQK9 was controlled by a dominant gene, tentatively named MePhyto. Throu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…For example, G-LecRK and WAK can both mediate resistance to Phytophthora spp. (oomycete) in tobacco and melon plants ( Wang et al 2020 ; Pi et al 2022 ). On the contrary, the expansion of Malectin-RK might benefit pathogen invasion in L. sativa , like the increased susceptibility to Hyaloperonospora arabidopsidis (oomycete) observed in Arabidopsis ( Hok et al 2011 ).…”
Section: Resultsmentioning
confidence: 99%
“…For example, G-LecRK and WAK can both mediate resistance to Phytophthora spp. (oomycete) in tobacco and melon plants ( Wang et al 2020 ; Pi et al 2022 ). On the contrary, the expansion of Malectin-RK might benefit pathogen invasion in L. sativa , like the increased susceptibility to Hyaloperonospora arabidopsidis (oomycete) observed in Arabidopsis ( Hok et al 2011 ).…”
Section: Resultsmentioning
confidence: 99%
“…The development of full genomic and transcriptomic sequences and new mapping approaches, such as genotyping by sequencing (GBS), and availability of core collections and Introgression Lines, produced a plethora of mapping studies (e.g., [14,15] and references therein). For example, Wang et al [16] mapped at high resolution downy mildew resistance in melon and identified a likely candidate, a receptor kinase gene; Giner et al [17] mapped CMV resistance, and we have finely mapped PRSV and Fusarium resistances [18].…”
Section: Introductionmentioning
confidence: 88%
“…Bulked segregant analysis sequencing (BSA-Seq) is a rapid and efficient approach that has been developed for the identification of major QTLs or genes associated with a given phenotype ( Michelmore et al., 1991 ; Kurlovs et al., 2019 ). BSA-Seq has been successfully used for mapping agronomically important loci in many plants, such as those associated with the branching habit trait in peanut ( Kayam et al., 2017 ), leafy head formation in Chinese cabbage ( Li R et al., 2019 ), genes controlling cold tolerance, QTLs controlling basal resistance to blast disease in rice ( Guo et al., 2020 ; Liang et al., 2020 ), candidate genes involved in the development of curd riceyness in cauliflower ( Zhao et al., 2020 ), a major QTL for shoot branching in Brassica rapa ( Li et al., 2020 ), and genes related to melon resistance in Phytophthora capsici ( Wang et al., 2020 ). Marker-assisted selection (MAS) is also an economical and efficient method, which has been successfully used in crops ( Chen et al., 2021 ; Zhang et al., 2022 ).…”
Section: Introductionmentioning
confidence: 99%